Israeli soldiers' intentions and actions toward seeking mental health help: Barriers and facilitators. Issue 2 (21st August 2022) - Schneider, Maayan; Werner, Shirli; Yavnai, Nirit; Ben Yehuda, Ariel; Shelef, Leah
Abstract: Background: While military settings may increase psychological distress, soldiers frequently avoid seeking professional help. This study aimed to examine barriers and facilitators associated with intentions to seek help and actually seeking help from a mental health officer (MHO) and how these differ among soldiers who had sought help in the past and those who had not. Method: This cross‐sectional study included 263 combat and noncombat soldiers. The Health Belief Model and the Help‐Seeking Model were the theoretical framework used to map the potential variables associated with soldiers' decision to seek help. Results: Stigma and administrative barriers were found to be significant barriers to both the intention to seek help and actually consulting an MHO. These findings were more definitive among combat soldiers. The belief in the effectiveness of mental health treatment was positively associated with the intention to seek help. Positive associations were found between well‐being, perceived seriousness of one's condition, and belief in the effectiveness of mental health care and intention to seek MHO help. Distress and self‐concealment were positively associated with actual consultation with an MHO. Public stigma about seeking help was associated with both the intention to seek mental health assistance and actually consulting an MHO. Conclusion: Military commanders should make an effort to make soldiers feel safe to seek mental health assistance by creating a supportive organizational atmosphere to reduce the stigma associated with mental health care.